KAJIAN KINERJA KEUANGAN BPR – ETAP DI JAWA BARAT DENGAN PENDEKATAN ECONOMIC VALUE ADDED - Edy Sukarno (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
This research aims to try to apply an alternative of EVA (Economic Value Added) method as a measurement of financial performance in the Conventional Rural Banks (BPR) industry. The motive of examining other alternatives because until now BPR financial performance measurement is still using a normative approach - Regulation of the Financial Services Authority (POJK) in the form of financial ratios. However, phenomenal happening reference numerals are not rigid. Some benchmark financial performance ratios such as ROA and Operational Expenses to Revenues (BOPO) applied during this magnitude resembles a commercial bank, whereas both business size is different. BPRs assume this spirit is still rough guide and constantly still in the process of looking for the best practice’s formulation. Empirically, this study calculating Economic Value Added (EVA) and using purposive sampling at 30 BPR in West Java for period 2013-2015 with the following criteria: (1) The total combined assets under 10 billion, (2) has information of financial ratios in 2013 -2015, (3) the results of the processing of statistical data meets the assumptions of classical test. In a panel data analysis here used 3 regression model, the model of common effect, fixed effect and random effect. Results of this research by F-test showed that all independent variables partially made a significant influence on the dependent variable EVA and by t-test showed that the independent variable EAT showed positive and significant effect on the variable EVA, but independent variable DER, CAR and DPK showed no significant effect on variable EVA. Prospects for implementing EVA method will lightened administratively in the measurement of BPR’s financial performance and potentially stimulate management tasks to focus on core banking activities.